2020
DOI: 10.3390/ijms21186911
|View full text |Cite
|
Sign up to set email alerts
|

NOX1 Inhibition Attenuates Kidney Ischemia-Reperfusion Injury via Inhibition of ROS-Mediated ERK Signaling

Abstract: The protective effects of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) 1 inhibition against kidney ischemia-reperfusion injury (IRI) remain uncertain. The bilateral kidney pedicles of C57BL/6 mice were clamped for 30 min to induce IRI. Madin–Darby Canine Kidney (MDCK) cells were incubated with H2O2 (1.4 mM) for 1 h to induce oxidative stress. ML171, a selective NOX1 inhibitor, and siRNA against NOX1 were treated to inhibit NOX1. NOX expression, oxidative stress, apoptosis assay, and mitoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Among the seven NOX isoforms [16], NOX1-dependent ROS production contributes to cellular growth signaling, angiogenesis, motility, and endothelial function [17][18][19]. NOX1 is a therapeutic target for IRI of multiple organs, including the heart, lung, kidney, and retina [12,[20][21][22]. ML171, a selective NOX1 inhibitor, has been studied in various animal models [11,23,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the seven NOX isoforms [16], NOX1-dependent ROS production contributes to cellular growth signaling, angiogenesis, motility, and endothelial function [17][18][19]. NOX1 is a therapeutic target for IRI of multiple organs, including the heart, lung, kidney, and retina [12,[20][21][22]. ML171, a selective NOX1 inhibitor, has been studied in various animal models [11,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we confirmed the renoprotective effect of ML171 in an ischemia-reperfusion injury (IRI) mouse model. ML171 attenuated kidney IRI via inhibition of ROS-mediated Extracellular Signal-Regulated Kinase (ERK) signaling and reduced oxidative stress-induced apoptosis in renal tubule cells [ 12 ]. These results suggest that ML171 could be used as a therapeutic agent for oxidative injury in many different organs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this current Special Edition, thirteen original research articles are presented: twelve in vivo studies in a murine or rat model and one in vitro study [ 3 ]. Seven studies show results from AKI models [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ], five from fibrosis models (or CKD models) [ 9 , 11 , 12 , 13 , 14 ] and two from a transplant rejection model [ 4 , 15 ] (two studies used two different in vivo models).…”
mentioning
confidence: 99%
“…The authors confirmed this effect through in vitro studies with immortal tubular epithelial cells [ 10 ]. Others used an IR model to show that the NOX1-selective inhibition attenuates kidney IR injuries via the downregulation of oxidative stress-mediated kinase signaling [ 8 ] or to investigate the autophagy dynamics during an IR injury, a potential treatment strategy due to removing damaged cells, macromolecules and organelles [ 6 ]. The effect of growth differentiation factor 15 (GDF15) was investigated in a murine model of anti-glomerular basement membrane glomerulonephritis [ 7 ].…”
mentioning
confidence: 99%